EFFECT OF OPEN AIR DRYING DURATION ON SEED MOISTURE AND THE THRESHING QUALITY OF COWPEA (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
To improve on the quality of threshed cowpea (Vigna unguiculata L.) produce by rural farmers in Ghana, variation in the duration of drying was employed. The cowpea was divided into five units and open air dried to 16.52, 14.69, 11.38, 9.69, and 8.36 % seed moisture contents (SMC) for three (3) days, five (5) days, eight (8) days, eleven (11) days and fourteen (14) days respectively after harvesting.  The SMC effect on threshing and seed quality was assessed with a developed cowpea thresher using 334, 435, 533, 634 and 735 rpm rotor speeds. The results showed that the throughput and efficiency increase with the speed and decreasing SMC. The percentage seed damage increases as the speed and SMC increase. The cowpea at 16.52 % SMC after drying produced the highest average seed damage of 3.05 % while 8.36 % SMC yielded 1.39% average seed damage. Analysis of variance (ANOVA) performed showed that there were significant differences (P Ë‚ 0.01) among the throughput capacities, seed damage and threshing efficiencies. However, there was no significant difference (P > 0.05) between the seed loss control of 9.69% and 8.36% SMC.  The minimum seed loss of 11.38%, 9.69% and 8.36% were less than the overall mean by 7.4, 20.6, and 29.4 % respectively. Therefore, the best machineâ€“crop parameter combination for optimal grain quality is 8â€“10 % SMC and rotor speeds of 388â€“550 rpm. To achieve these SMC, the crop must be dried in the open air for a minimum of eleven (11) days at 7 hour/day.